Dental fear and anxiety in older children: an association with parental dental anxiety and effective pain coping strategies - Coric A; Banozic A; Klaric M; Vukojevic K; Puljak L (Journal of Pain Research, 2014)
Anka Coric,1 Adriana Banozic,2 Miro Klaric,3 Katarina Vukojevic,4 Livia Puljak5 1School of Medicine, University of Mostar, Health Center Mostar, Mostar, Bosnia and Herzegovina; 2Laboratory for Pain Research, University of Split School of Medicine, Split, Croatia; 3Department of Psychiatry, School of Medicine, University of Mostar, Mostar, Bosnia and Herzegovina; 4Department of Anatomy, University of Split School of Medicine, Split, Croatia; 5Laboratory for Pain Research, University of Split School of Medicine, Split, Croatia Abstract: An association between dental fear and anxiety (DFA) has been confirmed for children younger than 8 years, but this association in older children is less clear. The aim of this study was to fill this knowledge gap by studying DFA in older children and their parents with validated measures. This cross-sectional study, conducted at Community Health Centre Mostar, Bosnia and Herzegovina, included 114 children and their parents. DFA, coping, and sociodemographic variables were studied using Corah Dental Anxiety Questionnaire (CDAS), Dental Subscale of the Children's Fear Survey Schedule (CFSS-DS), Dental Cope Questionnaire, and sociodemographic questionnaire. Maternal CDAS scores had significant positive correlation with child DFA measured with CFSS-DS (r=0.35, P<0.001) and CDAS (r=0.32, P<0.001). Fathers' CDAS scores were not associated with child CFSS-DS, but showed a moderate correlation with child CDAS (r=0.19, P<0.05). There were no significant differences in children's fear and anxiety based on age, sex, or socioeconomic variables. Children used internal coping strategies most frequently and external coping strategies were rated by the children as the most effective. We did not find differences in number and type of effective coping strategies in children with high DFA compared with children with low DFA. In conclusion, there is evidence of the coexistence of dental fear in parents and older children. These findings may help to devise interventions that will prevent or alleviate children's DFA. Keywords: fear of dental pain, pain behavior, coping skills, adaptive behavior, school children, parents